Salicylic acid as a peeling agent: a comprehensive review - Arif T (Dove Medical Press, 2015)
Tasleem Arif Postgraduate Department of Dermatology, STD and Leprosy, Government Medical College, Srinagar, Jammu and Kashmir, India Abstract: Salicylic acid has been used to treat various skin disorders for more than 2,000 years. The ability of salicylic acid to exfoliate the stratum corneum makes it a good agent for peeling. In particular, the comedolytic property of salicylic acid makes it a useful peeling agent for patients with acne. Once considered as a keratolytic agent, the role of salicylic acid as a desmolytic agent, because of its ability to disrupt cellular junctions rather than breaking or lysing intercellular keratin filaments, is now recognized and is discussed here. Salicylic acid as a peeling agent has a number of indications, including acne vulgaris, melasma, photodamage, freckles, and lentigines. The efficacy and safety of salicylic acid peeling in Fitzpatrick skin types I–III as well as in skin types V and VI have been well documented in the literature. This paper reviews the available data and literature on salicylic acid as a peeling agent and its possible indications. Its properties, efficacy and safety, the peeling procedure, and possible side effects are discussed in detail. An account of salicylism is also included. Keywords: acne vulgaris, desmolytic agent, melasma, photodamage, salicylic acid